Biogenic nanoparticles as a promising drug delivery system - Rehab M. Abdel-Megeed (Toxicology Reports)
Nanotechnology has significantly influenced the worldwide medical services sector during the past few decades. Biological collection approaches for nanoparticles are economical, non-toxic, and ecologically benign. This review provides up-to-date information on nanoparticle production processes and biological sources, including algae, plants, bacteria, fungus, actinomycetes, and yeast. The biological technique of generating nanoparticles has advantages over chemical, physical, and biological methods, including low-toxicity and friendly to the environment, thereby providing a viable option for therapeutic applications as s promising drug delivery system. In addition to aiding researchers, the bio-mediated, obtained nanoparticles also modify particles to promote both health and safety. We also looked at the important medicinal uses of nanoparticles, including their antifungal, antimicrobial, antiviral, antidiabetic, anti-inflammatory, and antioxidant properties. The current study highlights the findings of recent research in this field and discusses various methods proposed to describe the bio-mediated acquisition of novel nanoparticles.. The production of nanoparticles via biogenic sources possess various benefits, such as low cost, bioavailability, and environmental friendliness. In addition to the determination of the bioactive chemicals mediated by nanoparticle as well as the examination of the biochemical pathways and enzyme reactions. The major focus of this review is highlighting on the essential role of biogenic nanoparticles as promising drug delivery system.